Optimalisaasi Penerapan Sistem Pembayaran Digital Melalui QRIS Pada Street Food Stadion Mulana Yusuf di Banten - Kavin Fathul Adzim; Munawaroh Munawaroh (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The rapid development of information and communication technology has transformed the way people conduct transactions, including in the street food sector. QRIS (Quick Response Code Indonesian Standard), a national QR Code standard established by Bank Indonesia, is expected to facilitate digital transactions. However, the implementation of QRIS among street food vendors at Maulana Yusuf Stadium, Banten, faces various challenges, such as low understanding among vendors and difficulties experienced by consumers in using the system.This study aims to identify the obstacles faced by vendors and consume The results show that although QRIS offers convenience and efficiency in transactions, there are several barriers hindering its optimal use. The main challenges identified include the vendors' low understanding of QRIS mechanisms and the consumers' difficulties in scanning QR codes.The study concludes that more intensive education and socialization efforts are needed to improve users' understanding and trust in the system. With the right measures, QRIS has the potential to become an effective solution for simplifying transactions in the street food sector and supporting more inclusive and sustainable local economic growth